Potential Molecular Biomarkers of Vestibular Schwannoma Growth: Progress and Prospects - Zhang, Yu; Long, Jianfei; Ren, Junwei; Huang, Xiang; Zhong, Ping; Wang, Bin (Frontiers in Oncology, 2021)
Vestibular schwannomas (VSs, also known as acoustic neuromas) are relatively rare benign brain tumors stem from the Schwann cells of the eighth cranial nerve. Tumor growth is the paramount factor for neurosurgeons to decide whether to choose aggressive treatment approach or careful follow-up with regular magnetic resonance imaging (MRI), as surgery and radiation can introduce significant trauma and affect neurological function, while tumor enlargement during long-term follow-up will compress the adjacent nerves and tissues, causing progressive hearing loss, tinnitus and vertigo. Recently, with the deepening research of VS biology, some proteins that regulate merlin conformation changes, inflammatory cytokines, miRNAs, tissue proteins and cerebrospinal fluid (CSF) components have been proposed to be closely related to tumor volume increase. In this review, we discuss advances in the study of biomarkers that associated with VS growth, providing a reference for exploring the growth course of VS and determining the optimal treatment strategy for each patient.